2019
DOI: 10.1007/s12206-019-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Viscous heating and temperature profiles of liquid water flows in copper nanochannel

Abstract: Understanding nanoscale fluidic transport becomes increasingly important due to the rapid development of nanotechnology and nanofabrication. By using molecular dynamics (MD) simulations, we investigated the viscous heating of water flows in copper nanochannels. The two scenarios that were studied are Couette flows and Poiseuille flows. We observed the scale effects on the distribution of fluid density, streaming velocity, fluid viscosity, and temperature across the channel. The results revealed the significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Studies on systems consisting of liquid films and solid walls [91,97,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] extensively examined the velocity distributions and the shear stresses near the solid-liquid interface for either Poiseuille or Couette flow of Lennard-Jones fluids. These studies revealed the effects of several parameters, including the number densities of either the solid or the liquid molecules [91,97,104,106,107], the intermolecular potential between solid and liquid molecules [97,100,[104][105][106][107][108][108][109][110]113], the roughness of the solid surface [97,114,119], the gap between the solid walls [105], the molecular species constituting the liquid [110][111][112], and the pressure of the system [97].…”
Section: Hydrodynamic and Thermal Wall Slipmentioning
confidence: 99%
“…Studies on systems consisting of liquid films and solid walls [91,97,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] extensively examined the velocity distributions and the shear stresses near the solid-liquid interface for either Poiseuille or Couette flow of Lennard-Jones fluids. These studies revealed the effects of several parameters, including the number densities of either the solid or the liquid molecules [91,97,104,106,107], the intermolecular potential between solid and liquid molecules [97,100,[104][105][106][107][108][108][109][110]113], the roughness of the solid surface [97,114,119], the gap between the solid walls [105], the molecular species constituting the liquid [110][111][112], and the pressure of the system [97].…”
Section: Hydrodynamic and Thermal Wall Slipmentioning
confidence: 99%
“…For example, a shear force can be established by translating a wall with respect to another for viscosity calculation (Figure B). Additional experiment-inspired phenomena such as viscous flow in nanochannels, , in Situ nanoindentation, and stress tests can also be easily simulated using NEMD. The obtained results often demonstrate close agreements with the experimental data.…”
Section: Mass/ion Transport Metrologymentioning
confidence: 99%
“…The ATP utilized entirely by all beings for the direct transformation of mechanical energy and also actively supports other biological reactions [1]. In recent years, various authors [2][3][4][5][6] have examined the heat production of mammals via calorimetry, and presented that for the given nutrients, both combustion and animal metabolism expends the same amount of oxygen. According to previous research [7], it is found that living things can produce thermal energy via fat, and combustion of carbohydrates in the living body, and is identical to the oxidation of heat of these elements.…”
Section: Introductionmentioning
confidence: 99%